2018
DOI: 10.1136/bmjgh-2018-000939
|View full text |Cite
|
Sign up to set email alerts
|

Health system governance following devolution: comparing experiences of decentralisation in Kenya and Indonesia

Abstract: IntroductionDevolution reforms in Indonesia and Kenya have brought extensive changes to governance structures and mechanisms for financing and delivering healthcare. Community health approaches can contribute towards attaining many of devolution’s objectives, including community participation, responsiveness, accountability and improved equity. We set out to examine governance in two countries at different stages in the devolution journey: Indonesia at 15 years postdevolution and Kenya at 3 years.MethodsWe col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 58 publications
6
42
0
Order By: Relevance
“…Such observations in the Philippines are not unique. Other studies have likewise reported on how, for example, tribal affiliations rather than qualifications influenced the hiring of staff by local governments in Kenya [41], or how decisions for local health services in Indonesia and Kenya were made based on their appeal to the electorate [42,43], or how political interference in health planning in Tanzania led to a complex relationship between the local politician and the local government technocrat [44].…”
Section: Discussionmentioning
confidence: 99%
“…Such observations in the Philippines are not unique. Other studies have likewise reported on how, for example, tribal affiliations rather than qualifications influenced the hiring of staff by local governments in Kenya [41], or how decisions for local health services in Indonesia and Kenya were made based on their appeal to the electorate [42,43], or how political interference in health planning in Tanzania led to a complex relationship between the local politician and the local government technocrat [44].…”
Section: Discussionmentioning
confidence: 99%
“…One of the overall devolution goals in Kenya was to improve local accountability over the management of public resources [ 7 , 8 ]. Early post-devolution studies however reported that the structures established following devolution had limited avenues for public participation, with compromised community participation & accountability as well as the public losing local accountability to the county executives [ 7 , 16 , 31 , 32 ]. For instance, an earlier study reported that the vetting and public participation in the recruitment of senior government officials as required by law was conducted merely as a public relations exercise as there was limited capacity for the relevant structures to undertake this excercise [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intercountry analysis was aimed at identifying areas of thematic convergence while highlighting areas of difference. For example, in two countries where governance of the healthcare system had been devolved (Kenya and Indonesia) on different time scales, comparing data from the two sites allowed us to look at the influence of context under similar health system governance, whereas comparing data from those two sites to the others gave an idea of the influence of devolution on the intervention [33]. Throughout the analysis process, we looked for commonalities to see where similar contexts yielded similar results and where they differed, viewing both types of findings as valuable.…”
Section: Qrn Good Practicesmentioning
confidence: 99%
“…Throughout the analysis process, we looked for commonalities to see where similar contexts yielded similar results and where they differed, viewing both types of findings as valuable. Not all inter-country findings were generalized across all settings; some publications were limited to a sub-set [33][34][35][36][37]. A detailed example of empirical and conceptual transferability is captured in Table 4.…”
Section: Qrn Good Practicesmentioning
confidence: 99%